Multidimensional Scale of Motives for Postponing Parenthood (MSMPP-18): Development, factorial structure and psychometric properties - Małgorzata Szcześniak; Adam Falewicz; Daria Brodowska (Scientific Reports)
Abstract Being a parent can be one of the most fulfilling experiences, but also the most challenging. Its complexity is reflected in the fact that the very thought of becoming a parent often fills people with mixed feelings and leads them to postpone the decision to have their first child. Considering that there is no tool for measuring the motives for deferred parenthood, the aim of the research presented in this article was to create such a questionnaire and test how these motives are related to other psychological variables. Based on the EFA results (N1 = 301), we assumed that the Multidimensional Scale of Motives for Postponing Parenthood could have an 18-item and 6-factor structure (MSMPP-18). Two separate CFAs, performed in Studies 2–3 (N2 = 201; N3 = 184), supported our hypothesis, and provided evidence that motives for postponing parenthood can be empirically defined in six dimensions: (1) feeling of uncertainty and incompetence; (2) self-focus; (3) parenthood as a burden; (4) fear of change; (5) financial security concern; and (6) worry about a child’s future. The goodness-of-fit of a six-factor solution of the model is presented in Studies 2–3. Moreover, the analyses in Studies 2–3 showed that six motives fit the general concept of postponed parenthood, thus suggesting one higher-order postponed parenthood factor. Correlational results showed the nomological network of motives for postponed parenthood/overall score that were positively linked to higher procrastination, future anxiety, negativity/instability, and negatively associated with resilience, mentalizing, and life satisfaction. The psychological approach to the motives for deferred parenthood, carried out in a series of 3 studies, is important from the theoretical, empirical, and practical points of view. The MSMPP-18 appears to be a reliable instrument for measuring the six motives for postponed parenthood and the total score of delayed parenthood.